Using formative research to develop the healthy eating component of the CHANGE! school-based curriculum intervention - Boddy Lynne M; Knowles Zoe R; Davies Ian G; Warburton Genevieve L; Mackintosh Kelly A; Houghton Laura; Fairclough Stuart J (BMC, 2012)
Abstract Background Childhood obesity is a significant public health concern. Many intervention studies have attempted to combat childhood obesity, often in the absence of formative or preparatory work. This study describes the healthy eating component of the formative phase of the Children's Health Activity and Nutrition: Get Educated! (CHANGE!) project. The aim of the present study was to gather qualitative focus group and interview data regarding healthy eating particularly in relation to enabling and influencing factors, barriers and knowledge in children and adults (parents and teachers) from schools within the CHANGE! programme to provide population-specific evidence to inform the subsequent intervention design. Methods Semi-structured focus group interviews were conducted with children, parents and teachers across 11 primary schools in the Wigan borough of North West England. Sixty children (N = 24 boys), 33 parents (N = 4 male) and 10 teachers (N = 4 male) participated in the study. Interview questions were structured around the PRECEDE phases of the PRECEDE-PROCEED model. Interviews were transcribed verbatim and analysed using the pen-profiling technique. Results The pen-profiles revealed that children's knowledge of healthy eating was generally good, specifically many children were aware that fruit and vegetable consumption was 'healthy' (N = 46). Adults' knowledge was also good, including restricting fatty foods, promoting fruit and vegetable intake, and maintaining a balanced diet. The important role parents play in children's eating behaviours and food intake was evident. The emerging themes relating to barriers to healthy eating showed that external drivers such as advertising, the preferred sensory experience of "unhealthy" foods, and food being used as a reward may play a role in preventing healthy eating. Conclusions Data suggest that; knowledge related to diet composition was not a barrier per se to healthy eating, and education showing how to translate knowledge into behavior or action is required. The key themes that emerged through the focus groups and pen-profiling data analysis technique will be used to inform and tailor the healthy eating component of the CHANGE! intervention study. Trial registration Current Controlled Trials ISRCTN03863885